BOZORNING MUVAFFAQIYATSIZLIK SABABLARI VA DAVLATNING IQTISODIY TARTIBGA SOLISH STRATEGIYALARI - Namozov Olim Botirovich, Aminova Shaxnoza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the causes of market failures and the strategies of state economic regulation. Drawing on scientific studies, the authors demonstrate that active government intervention is essential in areas where the market alone falls short. The paper also reviews governmental strategies to address market failures and provides practical recommendations.